2011
DOI: 10.1007/s00726-011-1072-2
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron vacuum ultraviolet (VUV) photo-induced fragmentation of cyclic dipeptides radical cations

Abstract: Cyclic dipeptides, due to their chemical properties and various bioactivities, are very attractive for medicinal chemistry. Fragmentations of three simple cyclic dipeptides including cyclo(Gly-Gly), cyclo(Ala-Ala) and cyclo(Gly-Val) in the gas-phase are determined with synchrotron vacuum ultraviolet (VUV) photoionization mass spectrometry (VUV PIMS) and theoretical calculations. Cyclo(Gly-Gly) and cyclo(Ala-Ala) show the similar fragmentation pathways. The primary decomposition reactions of cyclo(Gly-Gly) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…At variance with the fragmentation of amino acids, DKP derivatives have attracted less attention. Zhang et al 11 reported the VUV photoinduced fragmentation of cyclo(alanyl-alanine), cyclo(glycyl-glycine) and cyclo(glycilvaline) up to 11 eV, while the fragmentation of a series of both protonated and deprotonated cyclo-dipeptides has been studied by Guo et al 12,13 . We have recently shown 9 that the VUV irradiation of cyclo(alanyl-alanine), cAA, a 2,5-DKP with two methyl groups as side chains, produces oxazolidinone intermediates as well as being an excellent source of CO and HNCO prebiotic species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At variance with the fragmentation of amino acids, DKP derivatives have attracted less attention. Zhang et al 11 reported the VUV photoinduced fragmentation of cyclo(alanyl-alanine), cyclo(glycyl-glycine) and cyclo(glycilvaline) up to 11 eV, while the fragmentation of a series of both protonated and deprotonated cyclo-dipeptides has been studied by Guo et al 12,13 . We have recently shown 9 that the VUV irradiation of cyclo(alanyl-alanine), cAA, a 2,5-DKP with two methyl groups as side chains, produces oxazolidinone intermediates as well as being an excellent source of CO and HNCO prebiotic species.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 At variance with the fragmentation of amino acids, DKP derivatives have attracted less attention. Zhang et al 11 reported the VUV photoinduced fragmentation of cyclo(alanyl-alanine), cyclo(glycyl-glycine) and cyclo(glycil-valine) up to 11 eV, while the fragmentation of a series of both protonated and deprotonated cyclo-dipeptides has been studied by Guo et al 12,13 We have recently shown 9 that the VUV irradiation of cyclo(alanyl-alanine) (cAA), besides being an excellent source of CO and HNCO prebiotic species can also produce oxazolidinone intermediates. In the same study, we proposed a model where the interaction among the oxazolidinone intermediate and other neutral and charged fragments released in the molecular decomposition of cAA + may lead either to the reconstruction of the cyclic cationic dipeptide or to the formation of longer linear peptide chains via almost barrierless processes, thus proposing a new mechanism for the formation of more complex biomolecules as oligo-peptides.…”
Section: Introductionmentioning
confidence: 99%